Droughts: Learning continuity and recovery - Somdeep Chatterjee; Neeraj Katewa (Asian Development Bank Institute (ADBI), 2024)
In this paper, we study the nuanced relationship between drought, academic performance, and the efficacy of preventive measures, focusing on two drought-prone regions from the states of Maharashtra and Karnataka in India. Utilizing an event study framework relying on difference-in-differences regressions, we address the recurrent and non-permanent nature of droughts, elucidating their impact on learning outcomes over time. In Maharashtra, which lacks preventive schemes, successive droughts lead to a significant drop in standardized test scores for math and reading skills, followed by intermittent recovery and further interruptions. The school dropout rate also exhibits a similar pattern. Contrarily, Karnataka's existing government-led preventive programs demonstrate resilience in academic achievement during drought periods.
Keywords: I21; O12; Q54; Q58; 330; climate variability; human capital investment; educational attainment